Effectiveness and safety of insulin glargine versus detemir analysis in patients with type 1 diabetes: systematic review and meta-analysis. (August 2018) - Silva, Thales B. C.; Almeida, Paulo H. R. F.; Araújo, Vania E.; Acurcio, Francisco de Assis; Guerra Júnior, Augusto A.; Godman, Brian; Alvares, Juliana
Background: Diabetes mellitus type 1 (DM1) is an autoimmune disease characterized by metabolic destruction of pancreatic cells responsible for insulin production, with treatment based on replacing insulin. Long-acting insulin analogs are indicated for patients with DM1 who exhibit important oscillations of their daily glycemia, despite its higher cost. Our study objective was to evaluate the effectiveness and safety of two long-acting insulins, insulin glargine and detemir, in treating patients with DM1. Methods: We undertook a systematic review with meta-analysis of observational studies (cohort and registry) available in the databases and the gray literature, and a complementary search in the Diabetes Care journal. Outcomes assessed were: glycated hemoglobin concentration; fasting plasma or capillary glucose; occurrence of episodes of severe hypoglycemia and occurrence of nocturnal hypoglycemia. The assessment of methodological quality was performed using the Newcastle score. The meta-analyses were performed on software Review Manager ® 5.2. Results: Out of 705 publications, 8 cohort studies were included. The quality of these studies was classified as high. In the meta-analysis, results regarding episodes of severe hypoglycemia ( p = 0.02) and fasting glucose ( p = 0.01) were in favor of detemir. The glycated hemoglobin ( p = 0.49; I 2 = 89) showed high heterogeneity and no statistically significant difference between the two. The meta-analysis of total insulin dose favored glargine ( p = 0.006; I 2 = 75). The rates of nocturnal hypoglycemia (NH) were evaluated only for one study and showed a significant reduction of NH after therapy with detemir, ( p < 0.0001). Conclusion: Although some outcomes were favorable to detemir insulin analog, it has not been possible to identify important differences of effectiveness and safety between the two analogs. These results can help in the current debate on the inclusion of long-acting analogs on the list of reimbursed medicines in Brazil, especially with the recent introduction of an insulin glargine biosimilar at a considerably lower price.